Hunting and trapping strategies in the coastal mountains of northern Lebanon during the Epipalaeolithic. (2nd September 2017) - Edwards, Yvonne; Garrard, Andrew; Yazbeck, Corine
Abstract : Relative to other regions of the Levant, our knowledge of the adaptations of Epipalaeolithic hunter-gatherers to the late Pleistocene environments of the coastal mountains of the central and northern Levant are extremely limited. However, recently excavations at two adjacent caves at Moghr el-Ahwal in the Qadisha Valley of northern Lebanon have provided a rich record, particularly of hunting and trapping strategies from the period following the Last Glacial Maximum (LGM) until the Bølling/Allerød interstadial. The dominant prey species, which varied in proportions through time, included: wild goat; roe, red and fallow deer; as well as fox, hare, squirrel and partridge. These document the exploitation of a wide spectrum of habitats, and demonstrate the expansion of forest cover through this period. Comparisons are made with food procurement strategies through the Epipalaeolithic in the wider region.